Single‐Atom Catalysts on Covalent Triazine Frameworks: at the Crossroad between Homogeneous and Heterogeneous Catalysis. Issue 7 (20th December 2022) - Iemhoff, Andree; Vennewald, Maurice; Palkovits, Regina
Abstract: Heterogeneous single‐site and single‐atom catalysts potentially enable combining the high catalytic activity and selectivity of molecular catalysts with the easy continuous operation and recycling of solid catalysts. In recent years, covalent triazine frameworks (CTFs) found increasing attention as support materials for particulate and isolated metal species. Bearing a high fraction of nitrogen sites, they allow coordinating molecular metal species and stabilizing particulate metal species, respectively. Dependent on synthesis method and pretreatment of CTFs, materials resembling well‐defined highly crosslinked polymers or materials comparable to structurally ill‐defined nitrogen‐containing carbons result. Accordingly, CTFs serve as model systems elucidating the interaction of single‐site, single‐atom and particulate metal species with such supports. Factors influencing the transition between molecular and particulate systems are discussed to allow deriving tailored catalyst systems. Abstract : This Review highlights single‐atom catalysis on covalent triazine frameworks (CTFs), thus focusing on the available insights on factors influencing nuclearity and coordination environment of metal species on CTFs and the effect on catalytic performance.